TPM Technopark Sdn Bhd / Nurul Amira Amir - Amir, Nurul Amira (2017)
Assalamualaikum w.b.t. My name is Nurul Amira Binti Amir. I am student from the Faculty of Civil Engineering UiTM Pasir Gudang. The main reason engineering students need to do Industrial Training (IT) is so they are well prepared for a graduate job in their chosen field. It is a chance for us to put what we have learned at university to work in the kind of real-life situations we will come up against when we start our career. First of all, this report is about my industrial training that I have been going through for two month, which is 8 weeks. The place where I having my industrial training is at TPM TECHNOPARK Sdn Bhd company. I choose this place as my location for industrial training is because this company is really good in construction and management. The reason I choose to do my internship locally because I believe that I will gain a lot of experiences which I have yet to explore whether it is related my course or anything that related to real life as an engineer. This internship is a great experience for me to learn and improve as well as to develop new sets of skills. Nevertheless, my experience having an industrial training at the TPM TECHNOPARK Sdn Bhd can really teach me about working condition and the working attitude in the organization itself. This report consists of four main chapters. In this report, I will tell about my company background, which is for me is a very basic thing to have in a report. This report also consists of organization chart, vision and mission of the company. All about the company is in the chapter one while in the chapter two consists of weekly summary based on my logbook that I have to write it everyday in my industrial training. In the chapter three, it is about a technical report. In that chapter, J tell about what I learned at TPM TECHNOPARK Sdn Bhd Company. All about the test on the site organization, documents and more also have been write down in this report. Last but not least, in the chapter four is about the conclusion of my report, which is about what do I get from undergo through the industrial training. That is all about my report that I can share about. I hope with this information can really taught you something about working for the contractor.